IDENTIFIKASI PERUBAHAN CURAH HUJAN DAN SUHU UDARA DI KOTA BENGKULU DAN KABUPATEN KEPAHIANG PROVINSI BENGKULU - Muslihah, Dina Whiri; Akmal, Saif (Megasains, 2024)
Climate change has far-reaching impacts in various regions of the world. The chance of extreme climate conditions in the form of high rainfall and drought is increasing as a result of climate change. Indonesia, which is in a tropical region and is a developing country, is vulnerable to being affected by climate change, so it is necessary to analyze climate change in Indonesia. This research analyzes climate change using extreme climate indices produced from the Expert Team for Climate Change Detection and Indices (ETCCDI) study. This index calculates changes in minimum temperature, minimum temperature, and rainfall. Statistical analysis using the Mann-Kendall method was also carried out to see whether or not there were changing trends in climate elements. The data used is data from the Bengkulu Meteorological Station as a representative of the Bengkulu City area which is on the coast and data from the Kepahiang Geophysical Station as a representative of Kepahiang Regency which is in the highland area. The data used is data for the period 1991 – 2020. The results of this research show that there has been a significant change in minimum temperature in both regions.